Maternal Complications and Prognostic Factors of Severe Pre-Eclampsia in Three University Hospitals of Yaoundé: A Study of 115 Cases - Mol Henri-Leonard ,; Metogo Ntsama Junie,; Ngo Dingom Madye Ange,; Metogo Mbengono Junette,; Essiben Félix,; Mbia Claude Hector,; Foumane Pascal,; Ze Minkande Jacqueline, (HEALTH SCIENCES AND DISEASE, 2024)
ABSTRACT Introduction. Severe preeclampsia can be life-threatening for both the mother and baby if left untreated, and typically requires immediate medical intervention. The aim of our study was describe the management of severe pre-eclampsia in 3 hospitals of Yaoundé. Methodology. We conducted a descriptive cross-sectional study studying files of patients admitted in intensive care for severe pre-eclampsia and its complications from September 2008 to September 2018 for the retrospective phase and patients with pre-eclampsia and/or its complications admitted in intensive care from the 1st of October 2018 to the 30th of May 2019 for the prospective phase in the intensive care units of the University Teaching Hospital of Yaoundé, the Central Hospital of Yaoundé and the Gynaeco-Obstetric and Paediatric Hospital of Yaoundé. Results. Our study concerned 115 cases. The most represented age group was [30-34] years old. The most common complications were: eclampsia (39%), HELLP syndrome (14%) and acute kidney injury (12%). One case of haemorrhagic stroke was registered. Caesarean section was performed in 69% of cases. Nicardipine (92%) and magnesium sulphate (81%) were the main drugs used. The maternal mortality rate was 3.5%. The main factors of poor prognosis were acute pulmonary oedema, Glasgow Coma score < 8, altered liver function and haemoglobin level < 7g/dl. Conclusion. Severe pre-eclampsia is a serious issue in our intensive care units. Identified poor prognostic factors found in the study could help improve the management of its complications. RÉSUMÉ Introduction. La prééclampsie sévère peut être mortelle pour la mère et le bébé si elle n'est pas traitée, et nécessite généralement une intervention médicale immédiate. L'objectif de notre étude était d'examiner la prise en charge de la pré-éclampsie sévère dans 3 hôpitaux de Yaoundé. Méthodologie. Nous avons mené une étude transversale descriptive étudiant les dossiers des patientes admises en soins intensifs pour une pré-éclampsie sévère et ses complications de septembre 2008 à septembre 2018 pour la phase rétrospective, et des patientes atteintes de pré-éclampsie et/ou de ses complications admises en soins intensifs du 1er octobre 2018 au 30 mai 2019 pour la phase prospective dans les unités de soins intensifs de l'Hôpital Universitaire de Yaoundé, de l'Hôpital Central de Yaoundé et de l'Hôpital Gynécologique, Obstétrique et Pédiatrique de Yaoundé. Résultats. Notre étude a concerné 115 cas avec un sex ratio de 2,33. Le groupe d'âge le plus représenté était [30-34] ans. Les principales complications constatées étaient; l'éclampsie (39%), le syndrome HELLP (14%) et l'insuffisance rénale aiguë (12%). Un cas d'accident vasculaire cérébral hémorragique a été diagnostiqué. Une césarienne a été réalisée dans 69% des cas. Le nicardipine (92%) et le sulfate de magnésium (81%) étaient les principaux médicaments utilisés. Le taux de mortalité maternelle était de 3,5%. Les principaux facteurs de mauvais pronostic étaient l'œdème pulmonaire aigu, le score de Glasgow < 8, le fonctionnement hépatique altéré et le taux d'hémoglobine < 7g/dl. Conclusion. La pré-éclampsie sévère reste une pathologie grave présente dans nos unités de soins intensifs. Les facteurs de mauvais pronostic identifiés pourraient aider à améliorer la prise en charge de ses complications.